Biological markers of cardiac damage are not related to measures of cardiac systolic and diastolic function using cardiovascular magnetic resonance and echocardiography after an acute bout of prolonged endurance exercise. Issue 10 (23rd October 2009) - Wilson, M; O'Hanlon, R; Prasad, S; Oxborough, D; Godfrey, R; Alpendurada, F; Smith, G; Wong, J; Basavarajaiah, S; Sharma, S; Nevill, A; Gaze, David; et al.
Abstract : Objectives: Seventeen male participants (mean (SD) (range): age 33.5 (6.5) years (46–26 years), body mass 80 (9.2) kg (100–63 kg), height 1.81 (0.06) m (1.93– 1.70 m)) ran a marathon to investigate the relationship between systolic function (using cardiac magnetic resonance (CMR)) and diastolic function (using echocardiography) against biomarkers of cardiac damage. Methods: Echocardiographic and cardiac troponin I (cTnI)/N-terminal pro-B-type natriuretic peptide (NTproBNP) data were collected 24 h premarathon, immediately postmarathon and 6 h postmarathon. CMR data were collected 24 h premarathon and at 6 h postmarathon. Results: Body mass was significantly reduced postmarathon (80 (9.2) vs 78.8 (8.6) kg; p<0.001). There was a significant E/A reduction postmarathon (1.11 (0.34) vs 1.72 (0.44); p<0.05) that remained depressed 6 h postmarathon (1.49 (0.43); p<0.05). CMR demonstrated left ventricular end-diastolic and end-systolic volumes were reduced postmarathon, with a preserved stroke volume. Left ventricular ejection fraction 6 h postmarathon significantly increased (64.4% (4.2%) vs 67.4% (5%); p<0.05). There were significant elevations in cTnI (0.00 vs 0.04 (0.03) μg/l; p<0.05) and NTproBNP (37.4 (24.15) ng/l vs 59.34 (43.3) ng/l; p<0.05) immediately postmarathon. Eight runners had cTnI elevations immediately postmarathon above acute myocardial infarction cutoff levels (≥0.03 μg/l). No correlations between cTnI/NTproBNP and measures of diastolic function (E, A, E/A, isovolumic relaxation time, E deceleration time and E/E′) or measures of systolic function (stroke volume or ejection fraction) were observed immediately postmarathon or 6 h postmarathon. Conclusions: Biomarkers of cardiac damage after prolonged exercise are not associated with either systolic or diastolic functional measures.